k-4k=-(k-8)-3(6-k)

Simple and best practice solution for k-4k=-(k-8)-3(6-k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k-4k=-(k-8)-3(6-k) equation:


Simplifying
k + -4k = -1(k + -8) + -3(6 + -1k)

Combine like terms: k + -4k = -3k
-3k = -1(k + -8) + -3(6 + -1k)

Reorder the terms:
-3k = -1(-8 + k) + -3(6 + -1k)
-3k = (-8 * -1 + k * -1) + -3(6 + -1k)
-3k = (8 + -1k) + -3(6 + -1k)
-3k = 8 + -1k + (6 * -3 + -1k * -3)
-3k = 8 + -1k + (-18 + 3k)

Reorder the terms:
-3k = 8 + -18 + -1k + 3k

Combine like terms: 8 + -18 = -10
-3k = -10 + -1k + 3k

Combine like terms: -1k + 3k = 2k
-3k = -10 + 2k

Solving
-3k = -10 + 2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-2k' to each side of the equation.
-3k + -2k = -10 + 2k + -2k

Combine like terms: -3k + -2k = -5k
-5k = -10 + 2k + -2k

Combine like terms: 2k + -2k = 0
-5k = -10 + 0
-5k = -10

Divide each side by '-5'.
k = 2

Simplifying
k = 2

See similar equations:

| 5=-3t | | 7-x*3=9+5*x | | x(62-x)=961 | | 40+12x=4 | | -0.8x^3-1.6x^2+4.1x+3.5=0 | | 9u-36=108 | | 7-x*3=9+x*5 | | 3-5z=33 | | 85+16m=229 | | 23-9x=22 | | 180=4x+35+6x-15 | | 5(cos(x))=0 | | 22t=32(t-2.25) | | 2r^3-8r^2=42r | | f(x)=x^2-7x+6 | | 9(2n-3)=9 | | 5x-8+48=90 | | 12+4(2-3)=32+1 | | 3p^2-5p+2=0 | | 2(-4x+5)= | | 5+6(x-1)=2(2x+2)+x | | 3[3-3(x+1)]+1=2(-20-x)2x+20 | | 45=3(w-12)+13 | | 3.6-1.2=-2.8(n-5) | | -7x-(-8x+7)=-3(x+5) | | 11x-2=2(5x-1)+x | | -3(x+3)=5x+3 | | solvex+6y=12fory | | 8x-7(x+3)=14-8 | | 3x+5=-29 | | x*-y+11=0 | | 2(-2d-3)=12 |

Equations solver categories